The Antibacterial and anti-biofilm effects of Sumac (Rhus coriaria L) fruits extracts against some multidrug-resistant pathogenic bacteria - Alaamery, sally k.; Al-Hayanni, Huda S. A. (Journal of the Faculty of Medicine Baghdad, 2022)
Background: The prevalence of multidrug-resistant bacteria and their contribution to increased morbidity and mortality due to the difficult-to-treat diseases caused by these bacteria, has demonstrated a need to develop and use alternative antimicrobial agents to control multidrug-resistant bacteria. There has been a growing interest in medicinal plants and herbs and their extracts for the discovery of new natural therapeutic alternatives. Therefore, this current study aimed to know the antibacterial activity of aqueous and alcoholic extracts of the Sumac (Rhus coriaria L) fruits against multidrug-resistant clinical bacterial isolates and the effect of these extracts on biofilm production as an important virulence factor. Materials and Methods: The Sumac (Rhus coriaria L) plant was selected for this study, and aqueous and alcoholic extracts were prepared from its fruits. They were tested against four multi-antibiotic resistant bacterial isolates that produce biofilms (Gram-positive and Gram-negative), namely Staphylococcus aureus, Enterococcus faecalis, Acinetobacter baumannii, and Pseudomonas aeruginosa which were isolated from Iraqi patients with wounds and burns in Medical City hospitals. Results: The current study proved that the aqueous and alcoholic extract of Sumac ( Rhus coriaria L ) fruit is effective as an antibacterial and anti-biofilm against the studied multidrug-resistant bacterial isolates at all tested concentrations with significant differences. The study also showed that the alcoholic extract is more effective as an anti-bacterial and anti-biofilm than the aqueous extract of the Sumac. Conclusion: The current study provides valuable results for the use of extracts of medicinal plants and herbs, including sumac extracts, to treat pathogenic bacteria that have become more resistant to antibiotics. These plant extracts also contain natural compounds that can be used without causing any harmful effects on patients.